OP0239 Pregnancy outcomes in patients with iga vasculitis. (12th June 2018) - Nossent, J; Raymond, W.; Keen, H.; Inderjeeth, C.; Preen, D.
Abstract : Background: IgA vasculitis (IgAV) is usually a self-limiting condition, but women with a history of IgAV are reported to have an increased risk of complications during pregnancy. There is however little international data regarding obstetric outcomes and risk factors for IgAV patients 1 . Objectives: To compare pregnancy outcomes between matched controls and patients hospitalised for IgA vasculitis in Western Australia (WA), where birth centres attached to public hospitals are the principal source for delivery of free midwifery-led care. Methods: Cohort study of IgAV patients (ICD-9-CM 287.0/ICD-10-AM D69.0) using non-exposed age-matched controls (1:3), where pregnancy-related events and outcomes (see table 1 for ICD codes) were extracted from state-wide hospital morbidity data for period 1980 to 2015. Results are presented as odds ratios (95% CI) versus controls. Results: Pregnancy-related contacts (n=1, 440) occurred in 49.5% of all female IgAV patients (n=347) and in 37% of all female controls (n=914). IgAV patients were younger at first pregnancy (23.7 vs 26.4 years, p<0.01) and had a higher overall mean number of hospital pregnancy contacts than controls (5.4 vs 3.1, p<0.001). IgAV patients experienced 168 uncomplicated live births, 93 complicated (including preterm) deliveries and 32 abortive pregnancies. The risk for abortion (OR 1.3, CI: 0.7 to 2.3), complicated delivery (OR 0.9, CI: 0.7 to 1.3) or classification as high-risk pregnancy (OR 0.94, CI: 0.74 to 1.24) was similar for IgAV patients compared to controls, despite a higher risk of hypertensive disorders (OR 4.4 CI2.1–9.1). Conclusions: In this large population-based longitudinal study, the risk for abortion or complicated pregnancies/deliveries was not increased for IgAV patients. The more frequent hospital contacts and increased risk of hypertension during pregnancy in IgAV patients had little impact on pregnancy outcome. Reference: [1] Tayabali S, Andersen K, Yoong W. Diagnosis and management of Henoch-Schonlein purpura in pregnancy: A review of the literature. Arch Gynecol Obstet2012;286:825–29. Acknowledgements: Supported by an unrestricted grant from the Arthritis Foundation of Western Australia. We acknowledge the contribution by Data Linkage WA. Disclosure of Interest: None declared